Developing a specific model to exploring the determinant of individuals’ attitude toward forest conservation - Maleknia, Rahim; Azizi, Reza; Hălălișan, Aureliu Florin (Frontiers in Psychology, 2024)
In the context of forest conservation, individuals' attitude can significantly influence their intentions and subsequent behaviors towards conserving forests. However, there is a research gap when it comes to understanding the determinants of individuals' attitude towards forests conservation. To address this gap, the present study aimed to investigate the influence of variables associated with values from value-belief-norm theory, awareness of consequences, and ascription of responsibility from norm activation model on individuals' attitudes as main determinant of behavior intention. The Data of study was collected from a sample of 200 students from Behbahan University, Iran.. through a questionnaire designed specifically for this purpose. The validity and reliability of questionnaire were confirmed. Structural equation modeling was employed to analyze the collected data. The findings of the study revealed that the examined variables were able to describe 88.6% of the variance in individuals' attitude towards forest conservation. Specifically, it was found that biospheric (ƛ= 0.097) and altruistic (ƛ= 0.385) values, ascription of responsibility (ƛ= 0.150), and awareness of consequences (ƛ= 0.380) had significant and positive effects on individuals' attitude towards forest conservation. On the other hand, egoistic values exhibited a significant and negative impact (ƛ= -0.071) on individuals' attitude. These research findings hold significant implications for planners and policymakers involved in forest conservation efforts. By understanding the factors that shape individuals' conservation attitudes, decision-makers can develop targeted strategies and interventions to strengthen positive attitudes towards forest conservation. Given the positive influence of biospheric values and awareness of consequences, developing awareness-raising programs to enhance individuals' environmental knowledge and the awareness of outcomes of their conservation actions can be considered as strategy to strengthen public's attitude and improvement their participation in forest conservation projects.